2022
DOI: 10.1108/ijlm-02-2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

A new taxonomy of fourth-party logistics: a lexicometric-based classification

Abstract: PurposeThis paper aims to elaborate on current research on fourth party logistics “4PL” by offering a taxonomy that provides a deeper understanding of 4PL service offerings, thus drawing clear frontiers between existing 4PL business models.Design/methodology/approachThe authors collected data using semi-structured interviews conducted with 60 logistics executives working in 44 “4PL” providers located in France. Using automatic analysis of textual data, the authors combined spatial visualisation, clustering ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…3.1 Effects of social capital's dimensions on NPD project performance Villena et al (2011) emphasized the contribution of relational capital to reducing monitoring costs and improving cooperation within the relationship. Trust between buyers and suppliers leads to cost reduction and higher efficiency in problem solving (Fattam et al, 2022;Saikouk et al, 2021;Stuart et al, 1998). Johnston et al (2004) revealed that the level of a supplier trust regarding a buyer enhances innovation, quality, long-term and short-term costs, and buyer satisfaction.…”
Section: Social Assets For Npd Involving Suppliersmentioning
confidence: 99%
See 1 more Smart Citation
“…3.1 Effects of social capital's dimensions on NPD project performance Villena et al (2011) emphasized the contribution of relational capital to reducing monitoring costs and improving cooperation within the relationship. Trust between buyers and suppliers leads to cost reduction and higher efficiency in problem solving (Fattam et al, 2022;Saikouk et al, 2021;Stuart et al, 1998). Johnston et al (2004) revealed that the level of a supplier trust regarding a buyer enhances innovation, quality, long-term and short-term costs, and buyer satisfaction.…”
Section: Social Assets For Npd Involving Suppliersmentioning
confidence: 99%
“…Second, strong structural network ties between buyer and supplier firms result into mutual benefits in terms of reduced costs, superior ability to innovate and reduced NPD time, when the partners build a trustworthy relationship (Bidault et al, 1998). Also, the use of structuring practices between both project teams creates interdependent social exchange when trust and respect are established (Fattam et al, 2022;Saikouk et al, 2021), thereby improving performance outcomes (Cousins et al, 2008).…”
Section: Social Assets For Npd Involving Suppliersmentioning
confidence: 99%